Penggunaan Model Pembelajaran Problem Based Learning (Pbl) untuk Meningkatkan Hasil Belajar IPS Siswa Kelas V SD Inpres Kayawu - Moningka, Marcellah Olviana; Rorimpandey, Widdy H.F H.F.; Tumurang, Hetty J. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to improve social studies learning outcomes for fifth grade students at SD Inpres Kayawu through the Problem Based Learning (PBL) learning model. The research method used is a type of Classroom Action Research which consists of 4 strands, namely planning, implementation, observation and reflection. The research subjects were 26 students in class V of SD Inpres Kayawu, consisting of 15 girls and 11 boys. Before conducting the research, it was found that only 35% of students were able to achieve the KKM. After implementing cycle I, an increase of 23% or 58% of students were able to reach the KKM was found. After continuing with cycle II, an increase of 27% was found from cycle I and 50% of the pre-test score, so the learning outcomes achieved in cycle II were 85% or it could be said to be successful. Based on the results of the research and discussion, it can be concluded that the use of the Problem Based Learning learning model can improve the social studies learning outcomes of fifth grade students at SD Inpres Kayawu